rhIGF-1 Therapy for Growth Failure and IGF-1 Deficiency in Congenital Disorder of Glycosylation Ia ( Deficiency) - Bradley S. Miller MD, PhD (Journal of Investigative Medicine High Impact Case Reports, 2013)
Background . Congenital disorders of glycosylation (CDG) are a group of rare disorders in which glycosylation required for proper protein-protein interactions and protein stability is disrupted, manifesting clinically with multiple system involvement and growth failure. The insulin-like growth factor (IGF) system plays an important role in childhood growth and has been shown to be dysfunctional with low IGF-1 levels in children with CDG type Ia ( PMM2 deficiency). Case report . A 3-year-old Caucasian male with failure to thrive was diagnosed with PMM2-CDG at 5 months of age. Initially, his length and weight were less than −2 standard deviation score, IGF-1 <25 ng/mL (normal 55-327 ng/mL), IGFBP-3 1.0 µg/mL (normal 0.7-3.6 ng/mL), and acid-labile subunit 1.3 mg/L (normal 0.7-7.9 mg/L). Despite aggressive feeding, he continued to show poor linear growth and weight gain. At 17 months, he underwent an IGF-1 generation test with growth hormone (0.1 mg/kg/d) for 7 days; baseline IGF-1of 27 ng/mL (normal 55-327 ng/mL) stimulated to only 33 ng/mL. Recombinant human IGF-1 (rhIGF-1) therapy (up to 130 µg/kg/dose twice daily) was initiated at 21 months of age resulting in an excellent linear growth response with height increasing from −2.73 to −1.39 standard deviation score over 22 months. IGF-1 and IGFBP-3 levels also increased. Conclusion . This is the first case report of rhIGF-1 therapy in a patient with PMM2-CDG. The child had an excellent linear growth response. These results provide additional in vivo evidence for IGF dysfunction in PMM2-CDG and suggest that rhIGF-1 may be a novel treatment for growth failure in PMM2-CDG.